Carbon and energy payback of variable renewable generation - Thomson, Rachel Camilla (The University of Edinburgh, 2014)
The continued drive to reduce Greenhouse Gas (GHG) emissions in order to mitigate climate change has led to an increase in demand for low-carbon energy sources, and the development of new technologies to harness the available energy in the wind, waves and tides. Many controversies surround these technologies, however, particularly with regards to their economic cost, environmental impacts and the implications of the variability of their output for security of the electricity supply. In order to make informed policy decisions on future developments of the electricity system, it is necessary to address these controversies and confirm the environmental, economic and social sustainability of these new renewable generators. This thesis specifically examines two key issues: whether new variable-output renewable energy generators actually deliver a net reduction in greenhouse gas emissions over their lifetimes, and whether they produce a viable energy return on energy investment. Although renewable energy sources are themselves ‘carbon free’, GHG emissions (and energy consumption) occur during the construction, maintenance and decommissioning of the generator infrastructure required to convert this energy into electricity. Furthermore, the variability of the output power from such generators has implications for the operation of the grid - there may be a requirement for additional reserve capacity and the increased part-loading of conventional plant is likely to reduce its operating efficiency. Carbon and energy paybacks are measures of the time required for a new renewable installation to offset these life cycle impacts. The work presented in this thesis examines both the life cycle impacts and the GHG emissions displacement of variable renewable generation, using Great Britain as a case study, in order to provide a basis for significantly more robust and reliable estimates of carbon and energy paybacks. The extensive literature survey concentrates on two key areas: current calculation methodologies and estimates for life cycle carbon and energy consumption of power generators; and the marginal emissions displacement of variable renewable generation. A detailed life cycle assessment of the Pelamis wave energy converter is presented, which sets the embodied carbon and energy in the context of the wider environmental impacts and includes an examination of the effect of different assumptions on the analysis results. In order to investigate the true emissions displacement of renewable generation, a historical analysis of real data from the National Grid was carried out, identifying the marginal displacement factor of wind power and taking into account the effect of the efficiency penalties of conventional plant. The findings of the analyses presented in this thesis are combined with information from the literature to examine the actual carbon and energy payback of existing renewable generation infrastructure on the British grid, and to provide detailed recommendations for future carbon and energy payback calculations.
Keywords: carbon; energy; footprint; Life Cycle Assessment; LCA; greenhouse gas; renewable; power generation